2011
DOI: 10.1073/pnas.1110474108
|View full text |Cite
|
Sign up to set email alerts
|

Socially transmitted gut microbiota protect bumble bees against an intestinal parasite

Abstract: Populations of important pollinators, such as bumble bees and honey bees, are declining at alarming rates worldwide. Parasites are likely contributing to this phenomenon. A distinct resident community of bacteria has recently been identified in bumble bees and honey bees that is not shared with related solitary bee species. We now show that the presence of these microbiota protects bee hosts against a widespread and highly virulent natural parasite ( Crithidia bombi ) in an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
702
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 715 publications
(753 citation statements)
references
References 50 publications
21
702
2
1
Order By: Relevance
“…Defence levels and the associated immune responses are likely to be moderated by a variety of factors, including sex [43], nutrition [2,3,44] and the presence of a microbiota [45,46]. We found that poor nutrition condition-here, pollen deprivation-influences the expressed immune response in workers of B. terrestris to C. bombi at several levels.…”
Section: Discussionmentioning
confidence: 76%
“…Defence levels and the associated immune responses are likely to be moderated by a variety of factors, including sex [43], nutrition [2,3,44] and the presence of a microbiota [45,46]. We found that poor nutrition condition-here, pollen deprivation-influences the expressed immune response in workers of B. terrestris to C. bombi at several levels.…”
Section: Discussionmentioning
confidence: 76%
“…Exposure to numerous alkaloid, terpenoid and phenolic compounds is lethal to Trypanosoma species, probably via interruption of protein synthesis, DNA intercalation, interaction with neurotransmitters or induction of programmed cell death [41,42]. Second, secondary metabolites could affect bee immune function, including by upregulating bee immune response [43], stimulating bees' endosymbiotic gut bacteria [44], causing physical or chemical changes to gut lining [45], or simply by inducing diuresis [17].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used a classification system of bacterial OTUs to separate core and non-core OTUs (Koch and Schmid-Hempel 2011a;Koch et al 2013;Cariveau et al 2014). We defined Neisseriaceae , Orbaceae , Lactobacillaceae , and Bifidobacteriaceae as core families for bumblebees in accordance with Kwong et al (2014) and Meeus et al (2015).…”
Section: Classification and Verification Of New Otusmentioning
confidence: 99%